Power flow solution of three-phase unbalanced radial distribution network - Ranjan, R.; Venkatesh, B.; Chaturvedi, A.; Das, D. (Taylor & Francis Group, 2004)
A simple algorithm is presented to solve three-phase unbalanced radial distribution network (RDN). It solves a simple algebraic recursive expression of voltage magnitude, and all the data are stored in vector form. The algorithm uses basic principles of circuit theory and can be easily understood. Mutual coupling between the phases has been included in the mathematical model. The proposed algorithm has been tested with several distribution networks and the result of an unbalanced RDS is presented in the article.